Analisis Media Monitoring dan Jaringan Program Lapak Ganjar untuk Mendukung Pemasaran Digital bagi UMKM - Arifa Rachma Febriyani; Fibriyani Nur Aliya; Liliek Budiastuti (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2024)
Lapak Ganjar is a program launched by the Governor of Central Java Ganjar Pranowo since July 2020 to help promote commodities for Central Java MSMEs, especially when facing economic challenges during the ongoing Covid-19 pandemic, via Instagram @lapak_ganjar. This program is developing to support digital marketing for MSMEs, not only MSMEs in Central Java, but also MSMEs in several other provinces. This research aims to describe the analysis of media monitoring and network of the Lapak Ganjar program to support digital marketing for MSMEs. Several relevant concepts are used in this research, including the concepts of digital marketing and electronic word of mouth (e-WOM). This type of research is quantitative descriptive with media monitoring and network analysis methods using brand24 and netlytic. Media monitoring analysis was carried out in the period June to July 2022. The results of media monitoring analysis via brand24 in that period revealed that the Lapak Ganjar program received positive sentiment from netizens, while Twitter analysis using Netlytic in June to July 2022 found a total of 2,013 tweets mentioning the word Lapak Ganjar with some relevant related keywords. Network analysis via Netlytic also displays cluster 1 which refers to the account most frequently referred to, namely the ganjaranapps account.